Kebijakan Pemerintah Provinsi Jambi Dalam Meningkatkan Kesejahteraan Masyarakat di Era Globalisasi - Suhendri Suhendri; Burlian Senjaya; Samia Elviria (Governance, JKMP (Governance, Jurnal Kebijakan & Manajemen Publik), 2023)
This study is intended to analyze the role of government to improve people's welfare in the era of globalization. The discourse of globalization gave rise to radical groups who thought the government did not need to intervene in development because it was carried out by the private sector and skeptics who stated that precisely because of its many negative impacts globalization became an important entry point for the role of the state. Using the skeptical concept, public policy becomes a means of government, especially regional governments in the era of regional autonomy to play their role, as was done in Jambi Province. This study uses a qualitative approach by analyzing public policies of the Jambi Province Government and community welfare data. After the data is collected, it is analyzed using qualitative data analysis. The study results show that local governments play an important role in exploiting opportunities and preventing the negative impacts of globalization. Through a series of innovative and solutive policies, the Jambi Province Government seeks to improve the welfare of the community by utilizing the local potential it has. The development of vocational schools based on competition and local excellence, accelerated construction of rubber asphalt factories, accelerated development of the Merangin Geopark area, establishment of smallholder mining areas, Batanghari river Clean and land restoration is under threat are among the programs carried out by the Jambi Province Government.